Assessment of the PAG-IBIG housing program (1986)
The PAG-IBIG housing program is assessed in terms of viability and the attendant factors of profitability, equity, efficiency and acceptability. The following are the major observations: (1) members gained more under the PAG-IBIG program than through -the banking system; (2) while interest dividends were uniformly applied to members according to their total distribution, the program discriminated against member borrowers whose incomes were less than n3,000.00 monthly; (3) lag time for NHMFC take-out has now extended to six months; and (4) compulsory membership has been openly criticized by the members. To be viable, the program must be modified to be acceptable to the majority of members.
Keywords: Public housing aspects; Pag-IBIG Fund